How priority ordering of offence codes undercounts gendered violence: an analysis of the crime survey for England and Wales - Pullerits, Merili (The British journal of criminology, 2024)
The Offence Classification System (OCS) of the Crime Survey for England and Wales (CSEW) applies a priority order of offences that undercounts violence. By prioritizing burglary and criminal damage above some types of assault, physical violence that co-occurs with property crimes is discounted from official counts of incidents and victims of violence. Analyzing CSEW data from 2010/11 to 2019/20, we find the OCS omits approximately 210,000 incidents of violence every year. Out of these incidents, 51 per cent are domestic violence against women, contributing further evidence to the CSEW’s gendered data gap. Socioeconomically disadvantaged victims are also disproportionately undercounted. Whilst prior research has highlighted the undercounting of violence prevalence and repetition in the CSEW, the OCS undercounts the concurrency of violence.